MIKROALBUMIN AIR KEMIH (URIN) PASIEN DM TIPE 2 - Emmy Wahyuni; Imam Budiwiyono (Indonesian Association of Clinical Pathologist and Medical laboratory, 2009)
Diabetic Nephropathy is one of several chronic complication of type 2 DM that could lead to end stage renal disease (ESRD). In type2 DM patients, about 85% of ESRD caused by diabetic nephropathy. Persistent microalbuminuria can be predictor for nephropathy. Earlydetection of microalbuminuria could be useful in improving an aggressive treatment to avoid ESRD and other macrovasculer disorder intype 2 DM patients. The purpose of this study was to describe the microalbuminuria profile in type 2 DM patients. A cross sectional studywas taken on 21 type 2 DM patients. Data were analyzed by descriptive analyzed (distribution, frequency, mean, standard deviation, ttest). P value < 0.05 was considered significant. This study reveals that frequency microalbuminuria was 78.9%. There was no differentage between microalbuminuria and normoalbuminuria. Duration of diabetes in microalbuminuria patients were more longer. Themean time is 45.3 (41) months and normoalbuminuria 36(16) months. The systolic and diastolic pressure in microlabuminuria washigher than normoalbuminuria. The body mass index between microalbuminurian and normoalbuminuria (P < 0.05) was significantlydifferent. In patient with microalbuminuria the mean of HbA1c value was 7.9(2.5) and in normoalbuminuria patient it was 9(1.8).There were no significant different of lipid profile between both samples. In this study was only found significantly different of body massindex between microalbuminuria and normoalbuminuria patients.